Efficiency of Different Approaches in Functional Endoscopic Sinus Surgery for Chronic Rhinosinusitis: A Comparative Study - M P Abhishek; Sileveru Chandra Mouli; Mudassar Ahmed Shariff; Maryada Sravani; Kirti Malik; Himani Dadwal; Rahul Anand (Wolters Kluwer Medknow Publications, 2024)
Objective: Current research compared traditional FESS, balloon sinuplasty, and powered instruments for CRS efficiency. Methods: A prospective comparison analysis of 150 CRS patients who received FESS. The surgical method divided the patients into three groups: Group A (conventional FESS, n = 50), Group B (balloon sinuplasty, n = 50), and Group C (powered instrumentation, n = 50). Primary outcome measures included symptom alleviation, measured preoperatively and six months postoperatively using the "22-item Sino-Nasal Outcome Test (SNOT-22)". Preoperative and six-month postoperative "Short Form 36 (SF-36)" Health Surveys assessed postoperative complications and the quality of life. Results: Balloon sinuplasty relieved symptoms better than FESS and powered instrumentation. Mean SNOT-22 scores reduced by 62.1% in the balloon sinuplasty group, much higher than the standard FESS and powered instrumentation groups (49.1% and 45.8%, respectively) (P < 0.001). Balloon sinuplasty had fewer postoperative problems than FESS and powered instrumentation, including bleeding, infection, and synechia. Conclusion: Balloon sinuplasty treats CRS better than FESS and powered instrumentation and has fewer postoperative sequelae. These data imply that balloon sinuplasty may be a preferred FESS surgical strategy for CRS, but patient-specific characteristics and disease severity must be considered. Current findings need to be confirmed by larger studies with longer follow-up periods to determine the best FESS surgical strategy for CRS.